2011
DOI: 10.1071/rd10230
|View full text |Cite
|
Sign up to set email alerts
|

Immunological mechanisms to establish embryo tolerance in early bovine pregnancy

Abstract: A well-balanced immunological interaction between mother and the semi-allogenic embryo is of particular importance. The objective of the present study was to analyse mechanisms of immune tolerance in bovine pregnancy during peri-implantation. Simmental heifers inseminated with either cryopreserved spermatozoa or seminal plasma were killed 12, 15 or 18 days after oestrus. Uteri were flushed for the recovery of conceptuses and the ipsilateral intercaruncular endometrium was sampled for gene expression analysis. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
38
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(49 citation statements)
references
References 48 publications
7
38
0
1
Order By: Relevance
“…Whereas the presence of multiple embryos decreased TNF and increased IL1B protein levels, TNF and IL1B gene expression did not change, which is consistent with data found on day 7 in single-embryo vs cyclic animals (Mansouri-Attia et al 2012, Oliveira et al 2013). In addition, we found that the presence of embryos in the uterus reduces the number of endometrial CD45 positive leukocytes, specifically in caruncular areas; this concurs with previous work carried out by Groebner et al (2011), although their study involved a more advanced development stage and the presence of a single embryo in the uterus. We have also demonstrated that total uterine fluid protein decreases with the number of live embryos recovered, which fits in with a type 4 validation (Muñ oz et al 2012).…”
Section: Response Models In the Uterine Fluid And Endometriumsupporting
confidence: 80%
See 1 more Smart Citation
“…Whereas the presence of multiple embryos decreased TNF and increased IL1B protein levels, TNF and IL1B gene expression did not change, which is consistent with data found on day 7 in single-embryo vs cyclic animals (Mansouri-Attia et al 2012, Oliveira et al 2013). In addition, we found that the presence of embryos in the uterus reduces the number of endometrial CD45 positive leukocytes, specifically in caruncular areas; this concurs with previous work carried out by Groebner et al (2011), although their study involved a more advanced development stage and the presence of a single embryo in the uterus. We have also demonstrated that total uterine fluid protein decreases with the number of live embryos recovered, which fits in with a type 4 validation (Muñ oz et al 2012).…”
Section: Response Models In the Uterine Fluid And Endometriumsupporting
confidence: 80%
“…Each gene is capable of producing heterogeneous protein molecules that can be further modified after translation (Katz-Jaffe & Gardner 2007). In fact, on days 12-13, although protein levels in uterine fluid or endometrial tissue may vary, embryo-induced changes in endometrial mRNA are scarce or nonexistent when only a single embryo is present (Forde et al 2011, Groebner et al 2011.…”
Section: Exploring Faster Endometrial Responses To the Embryomentioning
confidence: 99%
“…In bovine endometrium, mRNA expression in cells located around blood vessels also suggests expression in immune cells. In a recent study, a strong increase in IDO1 expression was observed in cultured bovine endometrial stromal and glandular epithelial cells after treatment with IFNT [67]. The lower increase in IDO1 mRNA observed on D15 and D18 of pregnancy compared to the IFNA2 treatment could be due to fine-tuned regulation of the maternal immune system during early pregnancy.…”
Section: Genes Showing Stronger Upregulation After Ifna2 Administratimentioning
confidence: 97%
“…In mammals, most of tryptophan was metabolized along the kynurenine pathway and tryptophan metabolism was closely correlated with pregnancy (Stone & Darlington 2002, Schröcksnadel et al 2006. During pregnancy, decreased tryptophan concentration and increased concentrations of kynurenines were observed in human plasma and in the uteri of mice and cows (Minatogawa et al 2003, Schröcksnadel et al 2006, Groebner et al 2011. Previous studies have found that tryptophan metabolism was mainly dependent on tryptophan 2,3-dioxygenase (Tdo2) and indoleamine 2,3-dioxygenase (Ido) (Stone & Darlington 2002).…”
Section: Introductionmentioning
confidence: 99%